1984
DOI: 10.1073/pnas.81.16.5160
|View full text |Cite
|
Sign up to set email alerts
|

Receptors for human gamma interferon: binding and crosslinking of 125I-labeled recombinant human gamma interferon to receptors on WISH cells.

Abstract: Purified recombinant human y interferon (HuIFN-y), labeled with 125I , was used to study receptors for HuIFN-y on human WISH cells. 1251_

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…A radiolabelled band corresponding to molecular weight 120000 was obtained by SDS-PAGE when '"I-IFN-y was cross-linked to adherent cells such as HeLa, WISH or foreskin fibroblasts. This result confimied previous studies (Sarkar & Gupta 1984). When '"I-IFN-y was cross-linked to its receptor on peripheral blood monocytes, the 120000 band was not seen and, instead, a faint band of M.W.…”
Section: Multiple Molecular Forms Of Type II Ifn Receptorsupporting
confidence: 88%
“…A radiolabelled band corresponding to molecular weight 120000 was obtained by SDS-PAGE when '"I-IFN-y was cross-linked to adherent cells such as HeLa, WISH or foreskin fibroblasts. This result confimied previous studies (Sarkar & Gupta 1984). When '"I-IFN-y was cross-linked to its receptor on peripheral blood monocytes, the 120000 band was not seen and, instead, a faint band of M.W.…”
Section: Multiple Molecular Forms Of Type II Ifn Receptorsupporting
confidence: 88%
“…Using 17,000 dalton, biologically active 32P-labelled IFN-y, a single class of high affinity IFN-y receptors was demonstrated by Scatchard analysis to be present on multi-passaged human keratinocytes. The ligand binding studies performed at 4°C revealed a specific, time dependent (plateau at 4-6 hours), and saturatable reaction, with the resultant Kd and receptorsicell (0.25 nM;19.8 x lo3, respectively) to be within the range of values previously reported characterizing IFN-y receptors on cells such as keratinocytes, fibroblasts, WISH cells, and monocytei macrophages (Nickoloff, 1987;Mariano et al, 1987;Anderson et al, 1982;Finbloom et al, 1985;Sarkar and Gupta, 1984;Celada et al, 1984;Orchansky et al, 1986). Moreover, the current results indicate that the number of high affinity IFN-y receptor sitesicell, as detected by ligand binding studies, was dependent on the growth characteristics of the cultured keratinocytes.…”
Section: Immunobiological Effects Of Growth Modulatory Treatmentssupporting
confidence: 65%
“…In vivo studies were done on PBL isolated from patients being treated with (20)(21)(22)(23)(24)(25) gl) were mixed with an equal volume of electrophoresis buffer (containing I mM dithiothreitol and 2-mercaptoethanol), boiled for 5 min, and subjected to sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) using 7.5% gels (18). Gels were dried under vacuum, and exposed to XAR film ( Cells were treated with IFN a2, and subsequent '25I-IFN a2 binding assays were performed as described in Fig.…”
Section: Methodsmentioning
confidence: 99%